Detección de factores de riesgo en un cultivo de papa a partir de mapas espaciales de calor de las variables pH y humedad sensadas a lo largo del terreno. - Díaz Quiroga, Cristian Mauricio; Rodríguez Gil, Fabian David (Universidad Antonio Nariño, 2022)
In this research project, it is proposed to carry out a spatial visualization (heat map) of the terrain, in which the pH and moisture variables that are present in the soil during the process of a potato crop are indicated, and thus observe how they influence the growth of the plant.